Maternal risk taking on the balloon analogue risk task as a prospective predictor of youth alcohol use escalation. (October 2015) - Banducci, Anne N.; Felton, Julia W.; Dahne, Jennifer; Ninnemann, Andrew; Lejuez, C.W.
Abstract: The transition from late childhood through middle adolescence represents a critical developmental period during which there is a rapid increase in the initiation and escalation of alcohol use. Alcohol use is part of a constellation of risk taking behaviors that increase during this developmental transition, which can be explained by environmental and genetic factors. Social learning theory (SLT) implicates observations of parental drinking in the development of alcohol use in youth. Parental risk taking more broadly has not previously been examined as a factor predictive of alcohol use escalation in youth across adolescence. The current study examined the relative contributions of maternal risk taking on the Balloon Analogue Risk Task (BART) and maternal alcohol use in the prediction of alcohol escalation among youth over three years. Participants were a sample of 245 youth (55.0% male, 49.6% Caucasian) who participated annually between grades 8 and 10, drawn from a larger study of adolescent risk taking. Within our sample, maternal risk taking, as measured by the BART, predicted increases in alcohol use. Interestingly, maternal alcohol use and other youth factors were not predictive of escalations in youth alcohol use. Our findings suggest the importance of considering maternal riskiness more broadly, rather than solely focusing on maternal alcohol use when attempting to understand youth alcohol use across adolescence. These findings emphasize the relevance of maternal risk taking as measured by a behavioral task and suggest a general level of riskiness displayed by mothers might encourage youth to behave in a riskier manner themselves. Highlights: Social learning theory implicates parental drinking in offspring consumption. Parental risk taking has not been examined as a predictor of offspring alcohol use. Maternal risk taking predicts youth drinking above and beyond maternal drinking.